SIFAT PAPAN PARTIKEL DARI KAYU MANGIUM - Suwandi Kliwon (Jurnal Penelitian Hasil Hutan, 2002)
Ten year old Acacia mangium wood species from Sukabumi area (West Java) was used as the raw material of exterior type particleboard glued with phenol formaldehyde.Single layered particleboard with density target of 0.5 - 0. 70 g/cm3 with its nominal thickness of 1.50 cm. The dimension of particleboard was 30 cm x 30 cm x 1.50 cm. The treatment of wood particle were three kinds i.e. unsoaked, soaked for 24 hours and 48 hours in cold water. The objective of the study was to determine the effect of treatments on the physical and mechanical properties of particleboard. The result indicated that the modulus of rupture (MOR), air dry internal bond, the thickness swelling after soaked during 2 hours and 24 hours in cold water, 3 hours after soaked in boiling water and 3 hours soaked in boiling water and dried (absolute dry), moisture content and density of mangium particleboard met the Indonesian National Standard for particleboard. The treatment of wood particle soaked in cold water is not recommended.